2021
DOI: 10.1186/s12889-021-10995-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in health status, healthcare utilization, and costs among individuals with elevated blood pressure: the LARK study from Western Kenya

Abstract: Background Elevated blood pressure is the leading risk factor for global mortality. While it is known that there exist differences between men and women with respect to socioeconomic status, self-reported health, and healthcare utilization, there are few published studies from Africa. This study therefore aims to characterize differences in self-reported health status, healthcare utilization, and costs between men and women with elevated blood pressure in Kenya. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It has been suggested that the female survival advantage after surgery may be attributable to better health-seeking behaviors among females than among males [23]. In Kenya, among patients with elevated blood pressure, females are more likely than males to have attended an outpatient visit in the last 12 months and be taking prescription antihypertensive medication [27]. In a Malawian household survey, too, females were more likely than males to report seeking care for an illness [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the female survival advantage after surgery may be attributable to better health-seeking behaviors among females than among males [23]. In Kenya, among patients with elevated blood pressure, females are more likely than males to have attended an outpatient visit in the last 12 months and be taking prescription antihypertensive medication [27]. In a Malawian household survey, too, females were more likely than males to report seeking care for an illness [28].…”
Section: Discussionmentioning
confidence: 99%